CONVERSION AND GLOBAL REACTION RATE COEFFICIENT IN THE ABSORPTION OF SO2 BY DIFFERENT TYPES OF LIMESTONE IN A FLUIDIZED BED REACTOR - Camargo, F. L.; Pagliuso, J. D.; Milioli, F. E. (Revista de Engenharia Térmica, 2003)
This work concerns the study of the effect of limestone type on SO2 absorption in a bench fluidized bed reactor plant. Conversion and global reaction rate coefficients were established for conditions typical to fluidized bed combustion of coal. The bench plant is a bubbling bed reactor 160 mm internal diameter using silica sand as bed material, fluidized by pre-heated air. In order to simulate conditions close to the fluidized bed coal combustion ambience, the fluidizing air is pre-heated at high temperature (850 oC) and SO2 is added to the fluidizing air in a concentration typical of the process (1000 ppm). All the particulate, i.e. silica sand and limestone particles, was fed to the bed in a narrow size distribution between two subsequent ASTM sieves (with 545 μm mean diameter). In transient batch experiments charges of limestone are quickly injected into the bed, while the consequent variations of the exit concentrations of SO2, CO2 and O2 are continuously recorded. Analysis were performed on the effects of the type of limestone in the process, taking into account possible reaction controlling resistances, and considering possible effects of the calcination on the sulfation process.